Pengaruh Kapasitas SDM, Pemanfaatan TI Dan Pengawasan Keuangan Terhadap Nilai Informasi Pelaporan Keuangan Pemerintah Daerah - Galuh Fajar Delanno; Deviani Deviani (Universitas Negeri Padang, 2013)
The value of local government financial reporting information is influenced by several factors: the capacity of human resources, the utilization of information technology, the control of regional finance and the system of internal control. The writer wanted to know the effect those factors to the value of local government financial reporting information. testing hypothesis used primary data. The techniques analysis of data used path analysis with the system of internal control, the capacity of human resources, the utilization of information technology and the control of regional finance as exogenous variable . The research found that the capacity of human resources, the utilization of the information technology, the control of regional finance and the system of internal have a significally give positive influence to the value of local government financial reporting information.. It is recommended to the local government to do a review about the capacity of human resources, the utilization of information technology, the control of regional finance and the system of internal control to make financial reporting so it has information value. Keywords: information value, the capacity of human resources, the utilization of information technology, the control of regional finance, the system of internal control.